Wild fire : a novel - DeMille, Nelson (New York : Warner Books, 2006)
"Detective John Corey of The lion's game, Plum Island, and Night fall returns in a new novel about a conspiracy to detonate nuclear bombs in two American cities, setting off a world war of unimaginable proportions"--Provided by the publisher.
Keywords: Corey, John (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Nuclear terrorism -- Fiction; Terrorism -- Prevention -- Fiction; Suspense fiction